A REVIEW ON ROLE OF TRPV CATION CHANNELS - Sharma, Deep; Rana, Rekha; Thakur, Kiran (Journal of Biomedical and Pharmaceutical Research, 2021)
The mammalian branch of the Transient Receptor Potential (TRP) superfamily of cation channels consists of 28 members. They can be subdivided in six main subfamilies: the TRPC (‘Canonical’), TRPV (‘Vanilloid’), TRPM (‘Melastatin’), TRPP (‘Polycystin’), TRPML (‘Mucolipin’) and the TRPA (‘Ankyrin’) group. The TRPV subfamily comprises channels that are critically involved in nociception and thermo-sensing (TRPV1, TRPV2, TRPV3, TRPV4) as well as highly Ca2+ selective channels involved in Ca2+ absorption/ reabsorption in mammals (TRPV5, TRPV6). In this review we summarize fundamental physiological properties of all TRPV members in the light of various cellular functions of these channels and their significance in the various diseases.